Moluscos de la expedición del RIV Edwin Link en las costas del Caribe mexicano - González, Norma Emilia (Universidad de Costa Rica, 1998)
A checklist of marine mollusc species mainly from deep-water localities off Mexican Caribbean shores is pre sented.Samples were obtained with a mechanical arm in 2-307 m during the. expedition of (hé RIV "Edwin Link", August 1990; the listinclud¡:s 59 species of Oastropoda, 17 species of Bivalvia, tbree species of Scaphopoda and three species of Polyplacophóra.